Implementación de una unidad reguladora de tensión CC de potencia de bajo costo basada en microcontrolador - Capitanio y Cols., Rene A (2019)
The present work aims to develop a Dc voltage output regulated with a topology called voltage Drop Diode unit (vDDu). The system is composed of two parts: a power circuit, and a signal processing circuit. The power board contains the responsible circuits to supply the contactor and the signal processing control board. The conditioned signals are processed in a micro-controller. The objective of the system is to maintain the voltage supply around 125 vDc +/- 4%, for a power of 25kW. Thereby supplying a PbaX telecommunication system that is isolated of the electrical network distribution with a battery array. The firmware was developed in the mPlab environment for the micro-controller 18F6620. The obtained results show that the proposed system is satisfactory and that it also presents a lower economic cost of implementation than the existent converter topologies.